Procesos simplificados en contratación pública: un imperativo en el sistema vigente de contratación - Pacheco Loaiza, Miguel Ángel (2015)
This research, entitled: "SIMPLIFIED IN PROCUREMENT PROCESSES: AN IMPERATIVE IN THE CURRENT SYSTEM OF ENGAGEMENT" and facing legal problems related to the lack of flexibility and streamlining procurement processes that are developed by Ecuadorian state through the institutions of the public administration. The problem under study is related to the fact that the Constitution of the Republic of Ecuador, incorporated principles of government effectiveness and efficiency, and coordination to the Organic Law of the National System of Public Procurement, determines objectives of that system, expedite and simplify the procurement to optimize results. However when analyzing the regulation that statute, it is observed that in the bidding process too lengthy terms are set for the submission of tenders for the qualification of the same, so these lapses too excessive are against the agility and simplification, and also affect the performance of the effectiveness and efficiency as constitutional principles in the administrative field. The work has been developed based on an extensive theoretical analysis that brings the study of concepts, scholarly opinions, constitutional, statutory and regulatory legal standards Ecuadorian law and comparative law, as well as results obtained by applying the techniques survey and interviews that gather the information necessary to support the submission of a proposal to reform the legal regulation of the Organic Law of the National System of Public Procurement, aimed at reducing the terms for submission of tenders and qualification in bidding process as a means to implement streamlined processes in the current procurement system in Ecuador